THE ROLE OF CONSTRUCTIVISM-BASED LEARNING IN IMPROVING MATHEMATICAL HIGH ORDER THINKING SKILLS OF INDONESIAN STUDENTS - Ani Minarni; E. Elvis Napitupulu (IKIP Siliwangi and I-MES, 2020)
To make students actively involved in learning to grasp mathematical higher-order thinking skills (MHOTS) is not easy. Meanwhile, the ability is so important for students to master for it takes place when students continue their studies to a higher level as well as work within a variety of professions, especially in the era of the industrial revolution such nowadays. Many factors affect students' thinking abilities, including learning factors. This study, which implemented constructivism-based learning, aims to investigate the role and contribution of constructivism-based learning approaches as well as mathematical prior knowledge (MPK) to the achievement of MHOTS of middle secondary school students. The data tested through Multivariate Analysis at the 0.05 significance level. In general, this study found that: (1) In the experimental class, the learning approach plays an important role in the way it increased students' MHOTS significantly. (2) The average contribution of constructivism-based learning to MHOTS was at the range of 18% to 57%. (3) Student activity in learning increased significantly. (4) In some cases, there is an effect of interaction between learning factors and MPK towards the achievement of MHOTS. The study recommended the teachers to have courageous in implementing constructivism-based teaching and learning to improve students’ MHOTS.